Формування готовності майбутніх учителів до розвитку критичного мислення школярів засобами іншомовної освіти - Солодовнік Іван; Solodovnik Ivan (Видавництво «Код», 2025)
Резюме. У статті теоретично обґрунтовано та практично окреслено особливості формування готовності майбутніх учителів до розвитку критичного мислення школярів у процесі іншомовної освіти. Закцентовано увагу на формуванні ключових компетентностей учнів, серед яких критичне мислення посідає одне з провідних місць.

Abstract. The article theoretically substantiates and practically outlines the features of forming the readiness of future teachers to develop critical thinking of schoolchildren in the process of foreign language education. The relevance of the topic is due to the needs of the New Ukrainian School, which focuses on the formation of key competencies of students, among which critical thinking occupies one of the leading places. The development of this quality requires future teachers to have appropriate training, the ability not only to teach educational material, but also to stimulate the intellectual activity of schoolchildren, to form the ability to work with information, analyze it, ask questions and make well-founded conclusions. Foreign language education has significant potential for the formation of critical thinking due to its intercultural, analytical and communicative nature. Working with authentic texts, solving problem situations, participating in discussions, analyzing cultural phenomena – all this creates favorable conditions for the development of thinking in students. The article describes the structure of the readiness of a future teacher, which includes motivational-value, cognitive, operational-activity and reflective components. Particular attention is paid to methodological conditions that ensure the effective formation of this readiness in the conditions of a higher education institution, in particular, the introduction of innovative educational technologies, individualization of learning, and the development of a reflective approach to professional growth. Among the recommended conditions are courses on the methodology of developing critical thinking, project activities, modeling pedagogical situations, and creating a safe educational environment. The appropriateness of using digital tools, online platforms and means of visualizing thinking is emphasized. The results of the study are summarized and the prospects for further scientific research are identified: development of tools for assessing student readiness, creation of typical models of classes with the integration of critical thinking, as well as adaptation of international experience to the needs of the Ukrainian education system.
Formation of future teachers’ readiness to develop critical thinking of schoolchildren by means of foreign language education
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: критичне мислення; готовність; майбутні учителі; іншомовна освіта; професійна підготовка; методичні умови